La santé interculturelle, outil de domination ? L’expérience des sages-femmes traditionnelles mexicaines - Mounia El Kotni (Anthropologie & Santé)
Drawing on ethnographic fieldwork in Southern Mexico with traditional indigenous midwives, I offer a critical analysis of Mexican intercultural health policies through the example of the Chiapas intercultural hospital. Designed to reconcile biomedicine and traditional medicine, in practice the hospital resembles an empty shell, where traditional midwives are invited to practice without receiving any salary, under the biomedical gaze. Far from promoting indigenous medical knowledge, the intercultural hospital is both a place and a health policy that reproduce structural violence and racist bias against traditional midwives. This experiment highlights the need for a critical approach to interculturality, even more pressing as younger, professional midwives are hired to replace traditional midwives, who are pushed towards the margins of the Mexican healthcare system.